2023
DOI: 10.3390/md21040228
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic and Phenotypic Diversity of Bacillus spp. from the Mariculture System in China and Their Potential Function against Pathogenic Vibrio

Abstract: Bacillus spp. could be one of the most suitable substitutes for the control and prevention of aquatic diseases. The occurrence of species population, antimicrobial character, and virulence diversity in Bacillus spp. recovered from the mariculture system in China between 2009 and 2021 were investigated, screening for probiotic Bacillus strains with good biological safety that can inhibit Vibrio parahaemolyticus, V. alginolyticus, V. harveyi, V. owensii, V. campbellii. The results showed that 116 Bacillus isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…The isolates that carried the tet(45) gene exhibited a susceptible phenotype to tetracycline. It has been reported that Bacillus isolates showed an antibiotic phenotype that was sensitive to tetracycline while the tetB detection rate was 100% [ 52 ]. This might be due to the presence of varied antimicrobial resistance mechanisms and many genetic factors required for the resistance phenotypes [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isolates that carried the tet(45) gene exhibited a susceptible phenotype to tetracycline. It has been reported that Bacillus isolates showed an antibiotic phenotype that was sensitive to tetracycline while the tetB detection rate was 100% [ 52 ]. This might be due to the presence of varied antimicrobial resistance mechanisms and many genetic factors required for the resistance phenotypes [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these toxin genes are well-known as a result of being studied and characterized and have been used to identify the toxin potential of Bacillus species (Lindbäck and Granum, 2015). Despite being mainly reported in widely recognized as 'not-safe' species of Bacillus cereus, several species of Bacillus have also been reported to have these genes (From et al, 2005;Yu et al, 2023). Owing to the diversity of genomic structure between Bacillus species and strains, the presence of one gene may existent in one species and be non-existent in another or even between strains within the same species (Rossi et al, 2018;de Magalhães, 2019;Zhang et al, 2022) with the possible presence of multiple toxin-encoding genes in a Bacillus strain (Jeżewska-Frąckowiak et al, 2017).…”
Section: Plant Growth-promoting Bacteria Safetymentioning
confidence: 99%